Synthesis and characterization of silver nanoparticles by thermal treatment method - Gharibshahi, Leila (2017)
Silver nanoparticles have many technological applications, for instance in biosensing, photonics, electronics, catalysis and antimicrobial applications. Various methods of synthesizing silver nanoparticles by using inorganic salts as metal precursors have been reported which are mostly complicated in preparation procedure, difficult to attain pure particles, and the methods produced toxic by-products that may harm the environment. In this study, a simple thermal treatment method was employed and successfully produced pure silver nanoparticles. An aqueous solution containing silver nitrate as a metal precursor and polyvinyl pyrrolidone (PVP) as capping agent, which was dissolved in deionized water at the room temperature, were prepared. This solution was dried at 80 ̊ C for 24 h to form brown colored transparent solid remained before it was crushed and ground in a mortar to form powder before calcination at 400, 500, 600, 700, and 800 ̊ C in the oxygen and nitrogen atmosphere for 3 h in succession to decompose organic matters and crystallized the silver nanoparticles. The Fourier transforms inferred spectroscopy (FT-IR) and the corresponding peaks of silver, which observed in the EDX analysis of the sample, confirmed the formation of pure silver nanoparticles. The silver nanoparticles have a cubic structure determined from the XRD spectra. The average particle size determined from a prominent XRD peak by the Scherer’s formula showed that the change in particle size was in a good agreement with the particle size determined by TEM images. The spherical silver nanoparticles have uniform morphology and particle size distribution. When the sample containing 50 mg metal precursor and 2% PVP calcined at 400, 500, 600, 700, and 800 ̊C, the particles size were 7.88, 5.57, 4.61, 3.75, and 3.29 nm respectively. The electrostatic repulsive force and thermal vibration are the main factors that silver nanoparticles become smaller not larger at higher calcination temperatures. At calcination temperature 600 ̊ C, the particles size decreased at 4.61, 2.92, and 2.49 nm when varied the PVP concentration at 2%, 3%, and 4% respectively and the size increased at 2.93, 3.73, and 4.61 nm when varied the silver concentration at 30, 40, and 50 mg respectively. The optical properties of silver nanoparticles were measured by means of UV-visible absorption spectrophotometer, which revealed the absorption peaks shifted between 407 and 450 nm depends on the calcination temperatures, PVP and silver nitrate concentrations. The conduction band energy of silver nanoparticles was calculated from the absorption peaks and was found the conduction band decreased with increasing particle size of the silver nanoparticles. Increasing the calcination temperature from 400 ̊ C to 800 ̊ C, the conduction bands were 2.75, 2.81, 2.83, 2.95, and 3.94 eV for theparticle size at 7.88, 5.57, 4.61, 3.75, and 3.29 nm, respectively. The conduction band increased with decreasing particle size due to weaker electrical attraction between conduction electrons and positively ionic core as the number of atoms or protons to form the smaller particle is fewer. By varying the PVP concentration from 2% to 4%, the conduction bands were 2.83, 2.88, and 2.94 eV for the particle size at 4.61, 2.92, and 2.49 nm, respectively. The conduction band due to change in precursor concentration at 30, 40, and 50 mg silver nitrate were 2.94, 2.92, and 2.83 eV for the particle size at 2.93, 3.73, and 4.61 nm. Therefore, it was concluded that modified thermal treatment method is a proper method to produce pure silver nanoparticles in which, the size and conduction band energy of produced silver nanoparticles can be controlled by controlling the calcination temperature, PVP concentration, and metal precursor concentration. The silver nanoparticles’ size decreases and the conduction band energy increases by increasing the calcination temperature and PVP concentration and by decreasing metal precursor concentration. The thermal vibration of silver nanoparticles increases by increasing the calcination temperature and since electrons surround silver nanoparticles, therefore, the electrostatic repulsive force between the metal particles and the thermal vibration of nanoparticles are the main factors of size decreasing at higher calcination temperature. Since the size decreases the number of atoms or protons, which form the particle decrease, therefore, the conduction band energy increases by increasing the calcination temperature due to the weaker electrical attraction between conduction electrons and positively ionic core of nanoparticle. It was also found that the nanoparticles’ size decreases by increasing the PVP concentration due to increasing the capping ability of PVP to stabilize the silver atoms and ions strongly and therefore reduce the agglomeration speed. Since the size decreases, the numbers of atoms or protons, which compose the nanoparticle decrease, therefore, the electrostatic attraction between conduction electrons and the positively ionic core of nanoparticle becomes weaker and the conduction band energy increase by increasing the PVP concentration. It was concluded that the nanoparticles’ size increases by increasing the silver nitrate concentration due to increasing Ag+ ions and the agglomeration speed in the samples according to decreasing the capping ability of PVP to stabilize the silver atoms and ions strongly. Since the size increases, the numbers of atoms or protons, which compose the nanoparticle increase, therefore, the electrostatic attraction between conduction electrons and the positively ionic core of nanoparticle becomes stronger and the conduction band energy decrease by increasing the silver nitrate concentration.